Testing the Effect of a Brief, Online and Tailored Intervention on Dietary Behaviors of Australian Adults: A Randomized Controlled Trial. (7th June 2021) - Haddad, Joyce; Hendrie, Gilly; Dickinson, Kacie; Golley, Rebecca
Abstract: Objectives: Using technology, nutrition messages can be tailored to individuals, which may enhance the effectiveness of online dietary behavior interventions. The study objective was to test whether a brief, online intervention using tailored nutrition messaging, supported by behavior change techniques, is more effective than a brief, online intervention using generic messages, in reducing discretionary choices (energy dense, nutrient poor foods and beverages) intake in a sample of Australian adults. Methods: A two armed randomized controlled trial was conducted from September to December 2019. The intervention group received two e-mails containing tailored nutrition messages, supported by behavior change techniques, over a 28 day period. The control group received similar e-mails using generic messages. Sociodemographic and dietary data were collected using a validated Short Food Survey at baseline and at follow-up. Statistical analysis used ANCOVA. Results: Final analysis included 1441 Australian adults, of which 77.3% were female, with a mean age of 50.8 (SD = 16.0) and Body Mass Index of 28.2 (SD = 6.3). There was no significant difference between delivering tailored or generic messages via e-mail, on discretionary choice intake at follow-up, after controlling for baseline discretionary choice intake ( P  = .49). Regardless of intervention group allocation, there was a decrease in mean intake of discretionary choices from baseline to follow-up (M = 4.2, SD = 3.9 vs. M = 3.1, SD = 4.0, respectively, P  < .001), with a small to medium effect (Cohen's d  = .28). Conclusions: The primary outcome of the study was discretionary choice intake after a 28 day brief, online intervention using tailored or generic messaging. The intervention was able to significantly reduce discretionary choice intake, however, the impact was not significantly enhanced by tailoring the intervention message. Other forms of tailoring or the inclusion of additional intervention features should be investigated to further enhance intervention effectiveness in future research. Funding Sources: The presented work had financial support from Flinders University through a research scholarship, and from CSIRO, Healthy Development Adelaide and the Commonwealth Scholarships Program through top-up scholarships.